Evaluation of Serum Levels of Hepatic Enzymes and Plasma Proteins between Different Types of Acute Viral Hepatitis (Bangladesh Journal of Medical Biochemistry, 2013)
This cross-sectional study was carried out in 80 serologically diagnosed cases of acute viral hepatitis to assess and compare the serum hepatic enzymes & plasma proteins between four different types (A,B,C,E), 20 in each group. Hepatitis E, hepatitis B and hepatitis C were more prevalent in males than that in females. The study showed that geometric mean of S.AST of all the four types differed significantly (F= 274.94, p